Fractures sustained by slipping on ice or snow: an epidemiological study of 50,500 fractures from the Swedish Fracture Register - Henrik Ivdal; Linnea Bergenholtz; Carl Bergdahl; Olof Wolf; Emilia Möller Rydberg (Acta Orthopaedica)
Background and purpose: Despite numerous patients sustaining fractures annually due to slipping on ice or snow, descriptive studies are scarce, which may result in less systematic management and prevention. We aimed to analyze fractures in adults sustained by slipping on ice and snow in Sweden using data from the Swedish Fracture Register (SFR). Methods: Data on all patients ≥ 18 years registered in the SFR between January 1, 2015 and December 31, 2022, with a fracture sustained by slipping on ice or snow was extracted. Descriptive statistical analyses were performed. Results: During the study period, 50,500 fractures were registered as sustained by slipping on ice or snow, representing 9% of all registered fractures in the SFR during the same period. 60% of the fractures affected the upper extremity. The mean age at the time of fracture was 61 years (18–105) and almost 70% of fractures were seen in women. The most common fractures were to the wrist (34%), ankle (18%), proximal humerus (11%), and hip (10%). Conclusion: Almost 1 in 10 fractures is sustained by slipping on ice or snow. The most common fractures are related to the wrist and the ankle. The majority of fractures affect the upper extremity, and two-thirds are sustained by women. Protective shoe wear, and better snow and ice clearance, could potentially have a large effect on injury prevention.